2020
DOI: 10.1007/s42729-020-00214-0
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Increases Leaf Chlorophyll Content and Iron Nutritional Efficiency and Reduces Iron Deficiency in Sorghum Plants

Abstract: The objective of this study was to evaluate the effect of silicon (Si) on iron (Fe) deficiency in sorghum plants grown in a nutrient solution, seeing that sorghum crops are sensitive to iron deficiency and Si may alleviate this deficiency. Nonetheless, the nutritional mechanisms underlying this process have not been fully elucidated in this plant species. Treatments were arranged in a 2 × 2 factorial scheme and completely randomized block design, in the absence or presence of Si (2 mmol L −1) and under Fe defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 21 publications
2
20
0
2
Order By: Relevance
“…The photosynthetic rate of leaves treated with silicon fertilizer was significantly higher than that treated with organic carbon fertilizer, which also reflected this ( Figure 2 ). It was reported that silicon increases leaf chlorophyll content, expands chloroplast, and upregulated genes related to light-harvesting complex II, which increases the photosynthetic rate ( Teixeira et al, 2020 ). This means that light energy is a critical environmental component impacting the metabolism, synthesis, and transport of photosynthetic products in crops.…”
Section: Discussionmentioning
confidence: 99%
“…The photosynthetic rate of leaves treated with silicon fertilizer was significantly higher than that treated with organic carbon fertilizer, which also reflected this ( Figure 2 ). It was reported that silicon increases leaf chlorophyll content, expands chloroplast, and upregulated genes related to light-harvesting complex II, which increases the photosynthetic rate ( Teixeira et al, 2020 ). This means that light energy is a critical environmental component impacting the metabolism, synthesis, and transport of photosynthetic products in crops.…”
Section: Discussionmentioning
confidence: 99%
“…The alleviating effect of Si on Fe deficiency has been shown in both Strategy 1 (dicots and non-graminaceous monocots with reduction-based Fe uptake; Gonzalo et al, 2013 ; Pavlovic et al, 2013 ; Bityutskii et al, 2014 ) and Strategy 2 (graminaceous monocots that exhibit chelation-based Fe uptake; Nikolic et al, 2019 ; Teixeira et al, 2020 ) plant species. Moreover, the Si-ameliorative effect on Fe deficiency was found to be species-specific and pH-dependent ( Gonzalo et al, 2013 ; Bityutskii et al, 2018 ).…”
Section: Interactions Of Silicon With Micronutrientsmentioning
confidence: 99%
“…However, among the treatments, Se recorded the maximum plant height, and stem diameter may be due to timely availability and efficient utilisation of Se and other nutrients (Witold et al 2008) that improved the catalytic action in plant and also resulted in early plant maturity. In addition, foliar application of Se alleviates the micronutrients deficiency in sorghum plants and favours biomass production , Teixeira et al 2020. Plant height and stem diameter of other plants was also enhanced by the application of trace elements in sandy soil with low fertility (Zeidan et al 2010, Khalid et al 2019.…”
Section: Original Papermentioning
confidence: 99%